Effect of Vitamin B12 supplementation on the Diabetic Peripheral Neuropathy- a Review - Amir, Saira; Amir, Bisma; Afzal, Nida; Amina; Javed, Tayyaba; Shad, Maheen (International Health Review, 2026)
Neuropathic pain is the unpleasant sensation due to lesion of nerves. It is common in patients with diabetes as fluctuations in blood glucose take a toll on the nervous system. Furthermore, high doses of metformin for the long duration in patients, with type 2 diabetes are found to interfere with the normal metabolism of the vitamin B12 in body that leads to its deficiency. Vitamin B12 is a water soluble vitamin found in our body responsible for the methylation, thus has a role in the myelin sheath and DNA synthesis. Deficiency of vitamin B12 has debilitating effect on the nerves which results in neuropathy. Various studies have been carried out to study whether Vitamin B12 has an effect on the nervous regeneration or can its use improve the diabetic or metformin induced neuropathy? In this paper, up-to-date evidence for effect of vitamin b12 supplementation on diabetic peripheral neuropathy has been studied and evaluated.